Structural adjustment program and its impact on Bangladesh public administration - Aminuzzaman, Salahuddin (Philippine Journal of Public Administration, 1994)
Bangladesh is one of the first South Asian countries to adopt the Structural Adjustment Program (SAP), a package of structural and policy reforms -sponsored by the World Bank and the International Monetary Fund (IMF). The SAP implemented in Bangladesh consists of policies concerning demand management, structural and institutional reforms whose major instruments include: (1) tight monetary policy through restrictions on credit in the form of savings and controls on both the public and private sector, and (2) high fiscal policy with cutbacks on government expenditures (mainly health, education and agriculture services) as its main feature. In the name of rationalizing the services and optimizing public resources, important public sector enterprises have been privatized while some have been downsized. The article argues that SAP and its policy components have to be reexamined and complementary programs for the disadvantaged social sector. have to be devised.